Investigation of the hydrogen spillover effect in platinum promoted cobalt/hollow carbon spheres - Masilo, Joy (My University, 2019)
The hydrogen spillover effect, as a mechanism to explain the promotion effect of noble metals on supported Co Fischer-Tropsch catalysts, has garnered increasing research attention. This is due to the enhanced Co reducibility and activity in Fischer-Tropsch catalysis when noble metals are incorporated. In this project, Pt was used as the noble metal promoter and hollow carbon spheres (HCSs) were used as a support for the encapsulation of the Co catalyst. A hard-templating approach was used for the synthesis of the HCSs. We explored polystyrene spheres as the template and resorcinol-formaldehyde (RF) as the carbon precursor. Monodisperse polystyrene spheres were synthesized, followed by the addition of RF on the polystyrene spheres. The resulting composite was carbonized at 600 °C and it was during the carbonization of RF that template-removal also occurred. This was because the polystyrene spheres decompose at ~400 °C therefore the extra step of template removal after carbonization was eliminated. The HCSs had a BET surface area of 416 m2/g, pore volume of 0.39 cm³/g, and pore size of 3.8 nm. The HCSs shell thickness was tuned by varying the amount of RF used and changing the alcohol used in the synthesis procedure. HCSs with shell thickness sizes in the range of 30 – 80 nm were confirmed using TEM. In addition, Co was encapsulated in the HCSs using the hard-templating method similar to the method employed in the synthesis of the HCSs. After template-removal and carbonization, Co@HCS and CoPt@HCS catalysts were obtained with nanoparticles that were well-dispersed. In addition, the shell (~30 nm) of the HCSs was used to separate the Co and Pt nanoparticles by encapsulating the Co nanoparticles and loading the Pt nanoparticles outside the HCSs to form the Co@HCS@Pt catalyst. The targeted percentage loading of Co was 10% and that of Pt was 0.5%. The TPR profiles obtained for the catalysts showed that the presence of Pt indeed enhanced the Co reducibility, in both CoPt@HCS and Co@HCS@Pt catalysts. Evidence of this was seen in the downward shift in the peaks related to Co3O4 to Co0 reduction, via the CoO intermediate, to lower temperatures. Primary hydrogen spillover, invoked when Co oxide and Pt are in intimate contact (CoPt@HCS), was more favourable in enhancing the reduction of Co oxide to the catalytically active Co phase, Co (hcp), and this was observed in the in-situ XRD data obtained, as it was the dominant phase at 350 °C. The enhancement can be attributed to the dissociation of hydrogen on Pt and its subsequent spillover to Co oxide occurring more readily due to the intimate contact between Pt and Co in the catalyst. Further, the Co reducibility in Co@HCS@Pt, where secondary hydrogen spillover was invoked due to the separation between Co and Pt, was less pronounced, and the catalytically active Co (hcp) phase was formed in lower amounts. The separation between Pt and Co resulted in a diminished spillover effect. Preliminary FT studies were undertaken which will be investigated further. The effect of hydrogen spillover was observed in the FT performance of the catalysts. After catalyst activation at 350 °C, the CoPt@HCS catalyst, due to a primary hydrogen spillover, showed the highest CO conversion rate which may be ascribed to the type of Co phase formed during catalyst activation. In-situ XRD confirmed that the dominant Co phase was the Co (hcp) phase which is highly catalytically active in the FT reaction. The effect of hydrogen spillover in Co@HCS@Pt was diminished, also in the FT reaction, due to the lack of synergism between Pt and Co, as a result of the distance between them. In addition, the presence of CO in the FT reaction may be detrimental to H2 dissociation on Pt, leading to a diminished adsorption of hydrogen and its subsequent spillover. This effect of CO is more pronounced when Pt and Co are separated in comparison to when they are in intimate contact. Evidence of hydrogen spillover was also observed in the selectivities of the catalysts when compared at similar levels of CO conversions which moved towards hydrogenated products.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Chemistry. University of the Witwatersrand, Johannesburg. May 2019